Evaluasi Peran Core Tax Administration System (CTAS) dalam Modernisasi Sistem Perpajakan - Sukma, Paradisa; Mubaraq, Muhammad Raihan; Ajiani, Ika Putri Fitri (Jurnal Aplikasi Perpajakan, 2025)
The modernization of tax administration is a strategic effort to enhance the effectiveness of tax collection and taxpayer compliance. One of the key instruments developed in this reform is the Core Tax Administration System (CTAS), a comprehensive digital platform that supports real-time processes including registration, reporting, assessment, payment, and tax supervision. This study aims to analyze the role of CTAS in supporting the modernization of tax administration in Indonesia through a literature review approach. Data were collected from relevant sources such as policy documents, official reports, and previous research discussing CTAS implementation and tax reform. The findings indicate that CTAS contributes to improved administrative efficiency, fiscal transparency, accuracy of tax data, and automation of compliance monitoring. However, its effectiveness largely depends on institutional readiness, the quality of human resources, inter-agency system integration, and consistent policy implementation. Therefore, CTAS is not merely a technical reform, but part of a broader structural transformation in tax administration. This study highlights that the success of tax modernization through CTAS requires continuous support in terms of regulatory frameworks, technological infrastructure, and capacity building of tax officials.